Artificial Nucleobase–Amino Acid Conjugates: A New Class of TAR RNA Binding Agents1. Issue 7 (15th January 2014) - Joly, Jean‐Patrick; Mata, Guillaume; Eldin, Patrick; Briant, Laurence; Fontaine‐Vive, Fabien; Duca, Maria; Benhida, Rachid
Abstract The human immunodeficiency virus type‐1 (HIV‐1) Tat protein stimulates transcriptional elongation. Tat is involved in the transcription machinery by binding to the transactivation response region (TAR) RNA stem‐loop structure, which is encoded by the 5′ leader sequence found in all HIV‐1 mRNAs. Herein, we report the rational design, synthesis, and in vitro evaluation of new RNA binding agents that were conceived in order to bind strongly and selectively to the stem‐loop structure of TAR RNA and, thus, inhibit the Tat/TAR interaction. We have demonstrated that the conjugation of modified nucleobases, able to interact specifically with an RNA base pair, and various amino acids allows these motifs to bind the target RNA selectively and in a cooperative manner that leads to the inhibition of viral replication in HIV‐infected cells.